The Effect of Relationship Marketing and Relationship Quality on Customer Loyalty (Bank Muamalat Indonesia) - Mujahidin, Mujahidin; Yusuf, Muhammad; Ardianto, Rian; Sutaguna, I Nyoman Tri; Sampe, Ferdianndus (Technium Social Sciences Journal, 2022)
This study aims to analyze the influence of Relationship Marketing And Relationship Quality On Customer Loyalty. Maintaining customer loyalty is needed in the company, but the most important thing is how the company's efforts in conducting relationship marketing (marketing relationship) and relationship quality (quality relationship) in realizing customer loyalty (customer) at Bank Muamalat. This study used the quantitative method with multiple linear regression analysis with 100 respondents using the slovin formula. The results showed that the relationship marketing variable X1 calculated t value (2,979) > table t value (1,986) which means that relationship marketing has a positive effect on variable Y (customer loyalty). The variable relationship quality X2 value t count (2.586) > value t table (1.986) which means that relationship quality (X2) has a positive effect on the variable customer loyalty (Y) with a significant level of 0.011 < 0.05. obtained acalculated F value of 31.024 > Ftable of 3.09 so that the value then F0 is rejected and F 1 received with a significant 0.000 < 0.05 (which is determined), it can be interpreted that together there is a significant influence between relationship marketing and relationship quality on customer loyalty.